(untitled) (Pakistan Journal of Science, 2022)
This research study was planned to explore the economic and immunological impact of ginger (Z. officinale) in commercial broiler chicks. One hundred and sixty (160) day old broiler chicks purchased form local hatchery were divided into four groups A,B,C and D; having 40 chicks in each group. Each group was further replicated four times with 10 chicks per replicate. Ginger extract @ 30, 40 and 50 ml/liter of drinking water was given to groups A, B and C respectively. Group D was kept as control. Data on body weight gain, feed intake and economics were recorded for each replicate of the respective groups. It was observed out that treatment groups gained significantly (P<0.05) higher body weight than control group. Significant (P<0.05) difference was noticed in mean feed intake in group B and C. Mean anti body titer against IBD was higher for group B and C. Whereas Mean anti body titer against ND was higher for group C. Mean feed cost per chick was not affected by any group. Gross return was significantly (P<0.05) better in all the treatment groups as compared to control group D. It was concluded that use of ginger extract had significantly improved the immunity and over all performance of commercial broiler chicks.